Handbook of indoor air quality management - Moffat, Donald W. (Prentice Hall, 1997)
This handbook brings you solutions to virtually any problem in the field. Leading U.S. and international experts help you to create and maintain safe and healthy environments in structures from hospitals to residences, and handle a range of questions from health and comfort effects and physiologic thresholds to ventilation measurement and employee programs. For answers on instrumentation, contaminants, codes, and guidelines--for the solutions you need to assess, design, and maintain healthy and productive indoor environments, Indoor Air Quality Handbook is the one source to have.